Accessible and Cost‐Effective Method of PDMS Microdevices Fabrication Using a Reusable Photopolymer Mold. Issue 21 (17th September 2018) - Bourguignon, Natalia; Olmos, Carol M.; Sierra‐Rodero, Marina; Peñaherrera, Ana; Rosero, Gustavo; Pineda, Pedro; Vizuete, Karla; Arroyo, Carlos R.; Cumbal, Luis; Lasorsa, Carlos; Perez, Maximiliano S.; Lerner, Betiana
ABSTRACT: This work describes a novel and cost‐effective method of polydimethylsiloxane (PDMS) microchips fabrication by using a printing plate photopolymer called Flexcel as a master mold (Fmold). This method has demonstrated the ability to generate multiple devices from a single master, reaching a minimum channel size of 25 μm, structures height ranging from 53 to 1500 μm and achieving dimensions of 1270 × 2062 mm 2, which are larger than those obtained by the known techniques to date. Scanning electron microscopy, atomic force microscopy, and profilometry techniques have been employed to characterize the Fmold and PDMS replicas. The results showed high replication fidelity of Fmold to the PDMS replica. Furthermore, it was proved the reusability of the Fmold. In our study, up to 50 PDMS replicas have been fabricated without apparent degradation of the mold. The feasibility of the resulting PDMS replica was effectively demonstrated using a microfluidic device for enhanced oil recovery analysis. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2018, 56, 1433–1442 Abstract : In this article, a novel and cost‐effective method for fabrication of PDMS microdevices with high‐resolution structures is introduced using a flexographic photopolymer mold. The proposed photopolymer allows the generation of molds with precise dimensions of the structures, reaching dimensions up to 1270 × 2062 mm 2 .